2021
DOI: 10.3390/jdb9030023
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-Dependent Activation of ERK Mediates Repression of Chondrocyte Fate during Calvarial Development

Abstract: Wnt signaling regulates cell fate decisions in diverse contexts during development, and loss of Wnt signaling in the cranial mesenchyme results in a robust and binary cell fate switch from cranial bone to ectopic cartilage. The Extracellular signal-regulated protein kinase 1 and 2 (ERK1/2) and Wnt signaling pathways are activated during calvarial osteoblast cell fate selection. Here, we test the hypothesis that ERK signaling is a mediator of Wnt-dependent cell fate decisions in the cranial mesenchyme. First, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Culturing lung explants with PD0325901, an inhibitor for MEK, results in increased Col2a1 expression and a widening of the cartilage condensations, but has no impact on Sox9 expression Yoshida et al (2020) . This is consistent with reports in other systems that show that mesenchymal phosphorylated ERK (a kinase downstream of MEK) opposes cartilage formation Oh et al (2000) ; Ibarra et al (2021) . The differences between the culture experiments and the mesenchymal knockouts likely reflect differences in dosage and spatial restriction.…”
Section: Control Of Cartilage Ring Formationsupporting
confidence: 93%
See 1 more Smart Citation
“…Culturing lung explants with PD0325901, an inhibitor for MEK, results in increased Col2a1 expression and a widening of the cartilage condensations, but has no impact on Sox9 expression Yoshida et al (2020) . This is consistent with reports in other systems that show that mesenchymal phosphorylated ERK (a kinase downstream of MEK) opposes cartilage formation Oh et al (2000) ; Ibarra et al (2021) . The differences between the culture experiments and the mesenchymal knockouts likely reflect differences in dosage and spatial restriction.…”
Section: Control Of Cartilage Ring Formationsupporting
confidence: 93%
“…A number of other mechanisms has been found to activate ERK in other contexts. For one, mesenchymal WNT signalling has recently been shown to activate pERK in the cranial mesenchyme, which then blocks Sox9 and Col2a expression and cartilage formation Ibarra et al (2021) . Non-canonical SHH signaling has been suggested to trigger calcium-induced extracellular signal-regulated kinases (ERK) activation Robbins et al (2012) ; Carballo et al (2018) .…”
Section: Control Of Cartilage Ring Formationmentioning
confidence: 99%
“…RUNX2 mRNA expression was not modulated during differentiation, but RUNX2 protein levels decreased during differentiation, confirming that miR-204 regulates RUNX2 post-transcriptionally [19]. During chondrogenic differentiation, we observed reduced levels of beta catenin, whose degradation is promoted by SOX9 [34], as well as reduced p-ERK levels, whose activation has been demonstrated to repress chondrocytic commitment [35]. Recently, it has been demonstrated that miR-204 blocks ERK pathway activation [36] and that the miR-204-5p/FOXC1/GDF7 axis regulates osteogenic differentiation [16].…”
Section: Discussionsupporting
confidence: 65%
“…ERK1/2 is a positive regulator for osteoblast differentiation and bone formation. Studies have shown that C3G may act through ERK1/2 signaling pathways in various cells ( Hu et al, 2021 ; Ibarra et al, 2021 ). Li et al (2016) developed ternary Mg-1Ca-xwt% Sr (x = 0.2, 0.5, 1.0, 2.0) Alloys as degradable implant materials in orthopedic field.…”
Section: Mechanisms Of Osteogenesis Of Mg Matrix Compositesmentioning
confidence: 99%